Modelling and Simulation of Polysilicon Piezoresistors in CMOS-MEMS Resonator for Biomarker Detection in Exhaled Breath - Rabih, A. (IEEE Computer Society, 2015)
This research studies longitudinal and transverse polysilicon resistors deposited in the maximum stress points of a CMOS-MEMS resonator for mass detection. The longitudinally mounted resistors were found to increase with the stress and giving maximum of resistance change of 10 to 23 O when the actuation voltage was varied from 50 to 180 V, while the transverse resistors were found to decrease from 0.8 to 0.4 O for the given voltages. Possible Wheatstone bridge configurations were studied to get the maximum output voltage, which was found to be 14 mV when two equal longitudinal resistors are connected with two equal external resistors to form a half bridge configuration. Â© 2015 IEEE.